Farewell to the 'childhood of man': ritual, seasonality, and the origins of inequality1. (18th June 2015) - Wengrow, David; Graeber, David
<x xml:space="preserve">Abstract</x> Evidence of grand burials and monumental construction is a striking feature in the archaeological record of the Upper Palaeolithic period, between 40 and 10 kya (thousand years ago). Archaeologists often interpret such finds as indicators of rank and hierarchy among Pleistocene hunter‐gatherers. Interpretations of this kind are difficult to reconcile with the view, still common in sociobiology, that pre‐agricultural societies were typically egalitarian in orientation. Here we develop an alternative model of 'Palaeolithic politics', which emphasizes the ability of hunter‐gatherers to alternate – consciously and deliberately – between contrasting modes of political organization, including a variety of hierarchical and egalitarian possibilities. We propose that alternations of this sort were an emergent property of human societies in the highly seasonal environments of the last Ice Age. We further consider some implications of the model for received concepts of social evolution, with particular attention to the distinction between 'simple' and 'complex' hunter‐gatherers.